Panbunga ni Soyosoy (The blooming of the Benguet Lily): A grounded theory of being a teacher in rural Benguet - Mandapat, Evangeline Rachel S. (Animo Repository, 2012)
This study established the character of the rural educational field and explored the impact of this context on rural teachers behavior and practices. Interviews with 36 teachers from nine rural schools of Benguet were the main source of data. Employing the grounded theory method, the basic social process of owning the rural teaching profession through adapting, complying, and owning emerged as rural teachers way of responding to the rural milieu that is distinguished by context-related conditions and educational structural challenges. The resulting outcomes of work, desire for progress, and unique challenges of the rural teacher surfaced as possible motivators to engage in the owning process in order to facilitate the attainment of learning objectives.